Etika Kepribadian dan Kode Etik Guru - Nurasia; Syarifah Huriyah; Rosdiana (CV Kalimasada Group, 2023)
The aim of this research is to find out how the personality ethics and code of ethics of teachers are used in learning at school. This research is qualitative research using a phenomenological approach. The data sources for this research are primary data and secondary data. The data collection techniques are through observation, interviews and documentation. The results of the research show that personality ethics and teachers' codes of ethics in the learning process at school greatly influence student behavior, both in the cognitive, affective and psychomotor domains.